3, 4-Methylenedioxymethamphetamine-assisted psychotherapy for treatment of chronic posttraumatic stress disorder: A randomized phase 2 controlled trial. (December 2018) - Ot'alora G, Marcela; Grigsby, Jim; Poulter, Bruce; Van Derveer, Joseph W; Giron, Sara Gael; Jerome, Lisa; Feduccia, Allison A; Hamilton, Scott; Yazar-Klosinski, Berra; Emerson, Amy; Mithoefer, Michael C; Doblin, Rick
Background: Posttraumatic stress disorder often does not resolve after conventional psychotherapies or pharmacotherapies. Pilot studies have reported that 3, 4-methylenedioxymethamphetamine (MDMA) combined with psychotherapy reduces posttraumatic stress disorder symptoms. Aims: This pilot dose response trial assessed efficacy and safety of MDMA-assisted psychotherapy across multiple therapy teams. Methods: Twenty-eight people with chronic posttraumatic stress disorder were randomized in a double-blind dose response comparison of two active doses (100 and 125 mg) with a low dose (40 mg) of MDMA administered during eight-hour psychotherapy sessions. Change in the Clinician-Administered PTSD Scale total scores one month after two sessions of MDMA served as the primary outcome. Active dose groups had one additional open-label session; the low dose group crossed over for three open-label active dose sessions. A 12-month follow-up assessment occurred after the final MDMA session. Results: In the intent-to-treat set, the active groups had the largest reduction in Clinician-Administered PTSD Scale total scores at the primary endpoint, with mean (standard deviation) changes of −26.3 (29.5) for 125 mg, −24.4 (24.2) for 100 mg, and −11.5 (21.2) for 40 mg, though statistical significance was reached only in the per protocol set ( p =0.03). Posttraumatic stress disorder symptoms remained lower than baseline at 12-month follow-up ( p <0.001) with 76% ( n =25) not meeting posttraumatic stress disorder criteria. There were no drug-related serious adverse events, and the treatment was well-tolerated. Conclusions: Our findings support previous investigations of MDMA-assisted psychotherapy as an innovative, efficacious treatment for posttraumatic stress disorder.